2021
DOI: 10.1037/xap0000385
|View full text |Cite
|
Sign up to set email alerts
|

Changing pace: Using implementation intentions to enhance social distancing behavior during the COVID-19 pandemic.

Abstract: the disease caused by the new strain of coronavirus has spread exponentially across the country. While the spread of this disease can be significantly slowed if people practice "social distancing," it is difficult to break old habits and acquire new behaviors at the needed speed. The purpose of this study is to challenge how health risk messages are currently communicated (specifically by considering how the Center of Disease Control (CDC) communicates its recommendations for social distancing) and suggest an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 43 publications
2
16
1
Order By: Relevance
“…This result may seem as somewhat unintuitive and does not align with later information regarding high vaccination rates of the third and fourth doses among people who are at high risk of contracting the disease and/or being severely affected by the virus [10]. However, research indicates that the psychological and behavioral mechanisms that enable the performance of a one-time behavior, even if it is not the first time it is being performed, and performing a repeated behavior periodically, are different [69][70][71]. This means that people who agree to take a specific additional shot (given a specific state of the pandemic), would not necessarily agree in advance to get a shot periodically (when future conditions and severity of the pandemic are unknown) and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…This result may seem as somewhat unintuitive and does not align with later information regarding high vaccination rates of the third and fourth doses among people who are at high risk of contracting the disease and/or being severely affected by the virus [10]. However, research indicates that the psychological and behavioral mechanisms that enable the performance of a one-time behavior, even if it is not the first time it is being performed, and performing a repeated behavior periodically, are different [69][70][71]. This means that people who agree to take a specific additional shot (given a specific state of the pandemic), would not necessarily agree in advance to get a shot periodically (when future conditions and severity of the pandemic are unknown) and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…A specific form of planning, known as implementation intentions or “if-then” plans ( Gollwitzer, 1999 ), has also been proposed as moderator the intention-behavior relationship, suggesting that individuals who plan may be more likely to follow through on their intentions. Studies have indicated that compliance with a interventions using if-then plans, leads to greater adherence to physical distancing guidelines ( Ahn et al, 2021 ; Bieleke, Martarelli, & Wolff, 2021 ).…”
Section: Integrated Theories: Developing Comprehensive But Parsimonio...mentioning
confidence: 99%
“…Such an approach together with judicious testing of contextual attributes such as location and target population may provide important evidence of the contexts in which interventions targeting social cognition constructs, such as attitudes and risk perceptions, are likely to have optimal efficacy. However, although a small number of randomized controlled designed interventions adopting techniques aimed at changing behavior through changes in social cognition theory constructs have been reported (e.g., Ahn et al, 2021 ; Keller et al, 2021 ; Okuhara et al, 2020 ; Smith et al, 2021 ), none have tested mechanisms of action using the proposed mediated effects. Given the paucity of this research we recommend the need for interventions based on social cognition theories that test mechanisms of action.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation intentions has been proven effective in various domains (see Gollwitzer & Sheeran, 2006 for a meta-analysis), including health behaviors (Armitage, 2016;Robinson et al, 2019;Silva et al, 2018) and remains to this day one of the most effective tools to promote costly behaviors such as regular physical exercise (Milkman et al, 2021). In the context of the COVID-19 pandemic, implementation intentions has been tested by an interventional study which demonstrated the effectiveness of this simple "if-then" plan formulations fostering greater compliance with social distancing measures (Ahn et al, 2021).…”
Section: The Present Research: Social Goals Implementation Intentionsmentioning
confidence: 99%